S55 Tissue resident MAIT cell phenotype in the upper airway. (11th November 2022) - Jabeen, MF; Qureshi, A; Ferry, H; Klenerman, P; Hinks, TSC
Abstract : Introduction: Mucosal associated invariant T (MAIT) cells are the most abundant anti-bacterial innate T cell subset within humans, enriched at mucosal barrier (≤10% of airway T-cells) and profoundly suppressed in the lower airway by corticosteroids in severe asthma. MAIT cells are activated by riboflavin metabolites presented via MHC-related protein 1 (MR1) and by cytokines. MAIT cells can also express a 'tissue repair' programme conferring immunoregulatory properties. This has been demonstrated in lower airway MAIT cells but nasal cells are yet to be fully characterised. The upper airway is of interest in severe asthma given the burden of sinonasal disease. The nasopharynx is a distinct compartment with unique microbiome – we therefore hypothesise that disruption of local environments with corticosteroid use and airways infection can alter MAIT cell phenotype. This study aims to define nasal MAIT cell phenotype and function in health with the view to extend these approaches to severe asthma. Methods: Nasal brushings were taken from healthy (n=8) and severe asthmatic (n=6) individuals and MAIT cell frequency determined (CD3+Va7.2+CD161+) by flow cytometry. Healthy nasal brushings and paired peripheral blood samples were enriched for lymphocytes by density gradient centrifugation prior to activation with TCR (5-OP-RU 10nM, 6 h) or non-TCR (IL-12/18, 50 ng/ml each, 20 h) directed stimulus. MAIT cell phenotype and cytokine production were characterised by Cytek Aurora spectral analyser. Results: Compared with peripheral blood, nasal MAIT cells possess a tissue resident memory phenotype at steady state (CD103, CD25 and CD69 high, p<0.01). These cells constitutively express Granzyme B and IL-17A, which is further induced following TCR dependent or independent stimulation. Conversely, following stimulation, peripheral blood MAIT cells produce an IFN-gamma (IL-12/18, p<0.05) and TNF (5OPRU and IL-12/18, p<0.01) biased response, alongside upregulation of granzyme B, CD25 and CD69. Within this small cohort to date no significant reduction in nasal MAIT cell frequency was observed in severe asthma. Conclusions: Nasal MAIT cells possess a tissue resident memory phenotype and are skewed towards an immunoregulatory functionality compared with their peripheral blood counterparts. Ongoing work will analyse airway MAIT cell responses in severe asthma through functional assays and transcriptomic analysis.